O paradigma moral nos colégios militares: da idealidade à condição pós-moderna - Coelho, Francisco Sérgio Marçal (2021)
The present research aims to substantiate the reasons for the creation of an Intervention Project in order to shed some light on the ambivalence between the pedagogical-moral project of the Colégio Militar do Brasil System (SCMB) and the practices and values put forward by liquid modernity or postmodernity. Within this perspective, the focus of this research is to discuss and analyse how students experience the values which are in the basis of the SCMB's pedagogical proposal before the confrontation of these values by the new paradigm. Thus, we intend to use as methodological parameters: a historical analysis of the genesis of morality in modernity; a documentary research of the military laws that outline institutional values, intertwining with the theoretical basis of the thinkers who use this theme in order to show the intimate connection with the traditions, costumes and practices of the Brazilian Army; applying questionnaires to identify whether the SCMB is successful in shaping the student community to its legal regimes and worldview, or whether, on the other hand, that worldview is anachronical in the face of new challenges. Based on this research, finally, to present the Intervention Project in order to constitute, with teachers and students, a permanent discussion forum on this theme and, thus, contribute to the citizen formation of those involved.